DISTRIBUTION AND FREQUENCY OF MALIGNANT LYMPHOMA AT RSUD DR. SOETOMO BETWEEN 2013 - 2023 - Sisca Meida Wati; Theresia Indah Budhy; Nadila Tahta Fidari; Amira Nazhifa; Najwa Aulina Zulfa; Ridholia Ridholia (FKG ULM, 2025)
Background: Malignant lymphoma is a type of cancer caused by the proliferation of abnormal lymphocyte cells. In Indonesia, Non-Hodgkin's Lymphoma is ranked seventh as the most common new malignancy, while Hodgkin's Lymphoma is ranked 27th. Information on malignant lymphoma in East Java, especially Surabaya, is still limited, especially for a period of more than five years. Therefore, a ten-year study was conducted to gain a more comprehensive understanding of its distribution and frequency. Purpose: To obtain an overview of the distribution and frequency level of malignant lymphoma cases at Dr. Soetomo Hospital, Surabaya in the period 2013-2023. Methods: This observational study with a descriptive approach involved 382 patients as samples, which were analyzed based on the variables of age, gender, type of work, area of residence, anatomical location of the tumor, and size of the tumor. Results: Non-Hodgkin's Lymphoma was found to more dominant (59.4%) compared to Hodgkin's Lymphoma (40.6%). Cases were more common in men (57.3%) than women (42.7%), with the largest age group being in the range of 51–60 years. The majority of patients came from East Java Province, especially Surabaya, and were most often found in individuals working in the private sector (28.8%). The most common anatomical location was the nodal area, with the most common tumor size being less than 2 cm in diameter. Conclusion: This study presents the latest data on the distribution of malignant lymphoma at Dr. Soetomo Hospital, Surabaya and is expected to be a reference for further epidemiological research. Keywords: distribution, frequency, hodgkin lymphoma, malignant lymphoma, non-hodgkin lymphoma